2000
DOI: 10.1007/s11926-000-0040-8
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines and adhesion molecules in the pathogenesis of vasculitis

Abstract: Upregulated adhesion molecule and cytokine expression on endothelial cells and infiltrating inflammatory cells occur in most vasculitis syndromes. These observations suggest that vasculitis is associated with pathologic activation of normal immune cell cytokine cascades. Abnormal expression of adhesion molecules and cytokines in vascular endothelium is a manifestation of endothelial dysfunction that can be triggered by a variety of stimuli, including infectious agents, immune complexes, and antiendothelial cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 45 publications
0
22
0
1
Order By: Relevance
“…It has been reported that serum levels of endothelial molecules such as adhesion molecules and EC-derived cytokines were elevated in patients with vasculitis. [27][28][29] Furthermore, vasculitis-affected small vessels seen in MPA may have dysregulated endothelial cell function. 30 In patients with MPA, the origin of the increased serum MIF levels seems to be cells that are capable of secreting MIF; 11,13,31 specifi cally, the endothelial cells and/or infl ammatory cells such as monocytes and neutrophils.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that serum levels of endothelial molecules such as adhesion molecules and EC-derived cytokines were elevated in patients with vasculitis. [27][28][29] Furthermore, vasculitis-affected small vessels seen in MPA may have dysregulated endothelial cell function. 30 In patients with MPA, the origin of the increased serum MIF levels seems to be cells that are capable of secreting MIF; 11,13,31 specifi cally, the endothelial cells and/or infl ammatory cells such as monocytes and neutrophils.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Becker et al showed that AAV patients have elevated serum MIF levels (Becker, Maaser et al 2006). Patients with vasculitis have increased serum levels of endothelial-related molecules, such as adhesion molecules and EC-derived cytokines (Bradley et al 1994;Johnson et al 1997;Sundy & Haynes 2000). Indeed, vasculitis-affected small vessels, such as those found in MPA, may have dysregulated EC function (Filer et al 2003).…”
Section: Mifmentioning
confidence: 97%
“…The cause of the majority of the vasculitides is unknown, and it is likely that a complex interaction between inherited determinants and environmental factors such as infections trigger the disease. Upregulated adhesion molecule expression on endothelial cells and infiltrating inflammatory cells occur in primary systemic vasculitis, and endothelial dysfunction is likely to be central to the mechanism through which adhesion molecules and cytokines contribute to the pathogenesis of vasculitis (2).…”
Section: Introductionmentioning
confidence: 99%